Dekonstruksi Pedagogi Feminin Islam Model Integratif Sayyidah Fatimah Sebagai Counter Narrative Feminisme Sekuler Dan Patriarki Tradisional - Alif Rohmah Nur Habibah; Rika Sartika; Ana Aprista (Education Reserach Center, 2025)
This study aims to examine the conceptual construction of al-mar’ah al-ṣāliḥah (the pious woman) through the exemplary figure of Sayyidah Fatimah as portrayed in Shahabiyah Haula Ar-Rasul by Shaykh Mahmud Al-Mishri. Employing a library research approach and content analysis method, the study explores both the characteristics of feminine piety and the educational role of Sayyidah Fatimah as a wife within the framework of Islamic education. The findings reveal that piety in women is not fragmented but rather manifests as a multidimensional integration of spiritual, moral, intellectual, and social values. Fatimah’s exemplary conduct emerges as an ethical praxis rather than mere normative compliance, offering a relevant model for contemporary Muslim women. The study contributes theoretically to the development of al-mar’ah al-ṣāliḥah as a holistic model in Islamic gender discourse and family education, while also offering practical implications for premarital education and Muslim women empowerment. Further research is recommended to incorporate empirical data and conduct cross-cultural comparative analysis to expand the relevance and application of this conceptual model.